2020
DOI: 10.1038/s41598-020-60827-4
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized carbon dioxide as a potential tool for decellularization of pulmonary arteries for transplant purposes

Abstract: Vascular bio-scaffolds produced from decellularized tissue offer a promising material for treatment of several types of cardiovascular diseases. these materials have the potential to maintain the functional properties of the extracellular matrix (ecM), and allow for growth and remodeling in vivo. the most commonly used methods for decellularization are based on chemicals and enzymes combinations, which often damage the ECM and cause cytotoxic effects in vivo. Mild methods involving pressurized co 2 -ethanol (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
1
21
0
2
Order By: Relevance
“…Transmission electron microscopy studies on scCO 2 -treated tissues revealed collagen fibrils displaying thickness and organization equivalent to the native tissue. Collagen fiber organization seemed intact, as confirmed by the density and parallel appearance of the collagen fibrils [15]. Our present investigation is concurrent with the previous report that scCO 2 -mediated production of tissue and organ scaffolds did not alter the elastic collagen fibers or ECM -or, more importantly, that of the native tissue -indicating that scCO 2 is the holy grail technology for the production of tissue and organ scaffold.…”
Section: Reportssupporting
confidence: 90%
See 1 more Smart Citation
“…Transmission electron microscopy studies on scCO 2 -treated tissues revealed collagen fibrils displaying thickness and organization equivalent to the native tissue. Collagen fiber organization seemed intact, as confirmed by the density and parallel appearance of the collagen fibrils [15]. Our present investigation is concurrent with the previous report that scCO 2 -mediated production of tissue and organ scaffolds did not alter the elastic collagen fibers or ECM -or, more importantly, that of the native tissue -indicating that scCO 2 is the holy grail technology for the production of tissue and organ scaffold.…”
Section: Reportssupporting
confidence: 90%
“…Tissue scaffold structure and the integrity of elastic fibers (as examined by histology) in scCO 2 -mediated production of tissue scaffold revealed an overall preserved morphology with parallel aligned continuous elastic fibers and without any differences between treated and untreated tissue [15]. In detergent-treated tissue samples, spacing between elastic fibers was more noticeable compared with the scCO 2treated tissues [15]. Transmission electron microscopy studies on scCO 2 -treated tissues revealed collagen fibrils displaying thickness and organization equivalent to the native tissue.…”
Section: Reportsmentioning
confidence: 98%
“…This approach yields a nearly intact decellularized tissue free of cells, lipids, and nucleic acids, proposing an alternative to traditional decellularization methods. Nevertheless, further in vitro and in vivo analyses need to be completed [125].…”
Section: Vascular Tissuementioning
confidence: 99%
“…Supercritical CO 2 has been used initially to gently sterilize natural materials and tissues [107]. In recent years, supercritical CO 2 decellularization was developed on vascular tissues [108], and most recently, processing of human skin and porcine skin has been reported.…”
Section: Physical Approachesmentioning
confidence: 99%